2018
DOI: 10.1155/2018/5394928
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Rupture as a Complication of Circumcision following Total Subcoronal Urethral Ligation

Abstract: Circumcision is one of the most commonly performed procedures and generally is considered a safe and minor surgery. However, serious and catastrophic complications may sometime occur if adequate attention is not paid to all aspects of this procedure. Bleeding is the most common early complication of circumcision and sometimes is controlled by applying sutures. We hereby report a case of urethral obstruction after deep suturing of the bleeding site performed at a district center that led to bladder rupture as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
(7 reference statements)
0
4
0
Order By: Relevance
“… 3 , 10 Bladder tamponade will happen all sorts of urologic surgery including open surgery and endoscopy surgery. 2 , 11 , 12 Blood clots will accumulate in bladder at the last, no matter bleeding appears in upper urinary tract or lower urinary tract, and this will result in bladder tamponade and urinary retention in succession, while a surgery is often indeed needed. 2 , 10 , 11 Studies have reported rectal tube, catheter irrigating syringe, 6-hole irrigation catheter which were all successfully used for clot retention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 , 10 Bladder tamponade will happen all sorts of urologic surgery including open surgery and endoscopy surgery. 2 , 11 , 12 Blood clots will accumulate in bladder at the last, no matter bleeding appears in upper urinary tract or lower urinary tract, and this will result in bladder tamponade and urinary retention in succession, while a surgery is often indeed needed. 2 , 10 , 11 Studies have reported rectal tube, catheter irrigating syringe, 6-hole irrigation catheter which were all successfully used for clot retention.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 11 , 12 Blood clots will accumulate in bladder at the last, no matter bleeding appears in upper urinary tract or lower urinary tract, and this will result in bladder tamponade and urinary retention in succession, while a surgery is often indeed needed. 2 , 10 , 11 Studies have reported rectal tube, catheter irrigating syringe, 6-hole irrigation catheter which were all successfully used for clot retention. 13 , 14 Recently, with the enormous development of intracavity technique and equipment, the majority can be managed by transurethral clot evacuation using cystoscopes sheath or resectoscope sheath and Ellik flusher, except a few who underwent long time bleeding resulting in hematoma which need open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…10 In addition, published case reports on similar conditions ultimately resorted to surgical intervention to as a course of management. [2][3][4][5][6][7][8][9] Most authors report that an open approach but some have advocated for a laparoscopic approach to repair bladder ruptures. 6 In any case, the repair is performed from outside the bladder.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of literature, only three such cases were reported with this being the fourth. [3][4][5] We would like to report on a 7-day-old patient that suffered from an intraperitoneal bladder rupture following neonatal male circumcision.…”
Section: Introductionmentioning
confidence: 99%